On the complexities of modeling HIV/AIDS in Southern Africa - Nyabadza, Farai (Mathematical Modelling and Analysis, 2008)
In this paper problems associated with the modeling of HIV/AIDS in Southern Africa are presented. A mathematical model is presented to highlight the three major challenges of modeling HIV/AIDS, i.e condom use, vertical transmission and treatment. The model analysis for the case, where the treatment parameter ñ = 0, is presented in terms of the model reproduction number R and threshold parameters RT and RA that show the contribution of vertical transmission. It is shown that if R, RT, RA